1999
DOI: 10.1063/1.123716
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the electron energy distribution function in an argon radio-frequency discharge in the γ mode

Abstract: The α–γ transition in an argon radio-frequency discharge has been measured using Langmuir probes and a current–voltage monitor. At two pressures, bi-Maxwellian electron energy distribution functions were measured in the γ mode. Increasing the gas pressure results in a decrease in the high-energy component of the electron energy distribution function. A transition region in the current–voltage characteristic is also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
2
14
1
Order By: Relevance
“…Similar results and conclusions have been obtained by other groups. [4][5][6][7][8] The bi-Maxwellian eedf also has been obtained during computer simulation and modeling studies of capacitively coupled rf discharges in argon and other gases. [9][10][11][12] Godyak and co-workers have stated that the limitations of the energy resolution and range of Langmuir probes make determination of low-energy electrons and detection of relatively high-energy electron tails difficult for some discharge conditions.…”
Section: Observations Of Bi-maxwellian and Single Maxwellian Electronmentioning
confidence: 99%
“…Similar results and conclusions have been obtained by other groups. [4][5][6][7][8] The bi-Maxwellian eedf also has been obtained during computer simulation and modeling studies of capacitively coupled rf discharges in argon and other gases. [9][10][11][12] Godyak and co-workers have stated that the limitations of the energy resolution and range of Langmuir probes make determination of low-energy electrons and detection of relatively high-energy electron tails difficult for some discharge conditions.…”
Section: Observations Of Bi-maxwellian and Single Maxwellian Electronmentioning
confidence: 99%
“…Seo et al have also studied the effect of rf power on EEDF, claiming the evolution of EEDF is caused by the change of heating mode (from ohmic to stochastic and E-H transition) in a planar argon ICP discharge [13,14]. In a capacitively coupled rf discharge, Deegan et al reported that an increase of rf power induces an α-γ mode transition and the EEDF evolves from a Druyvestyn to a bi-Maxwellian distribution [15]. Seo et al also studied the effect of a sheath boundary on EEDF by changing the applied dc bias voltage on the substrate in an unbalanced planar type dc magnetron system [16].…”
Section: Introductionmentioning
confidence: 99%
“…Secondaries are always emitted, as can be seen in figures 2(c) and (d), displaying a transition from Druyvesteynlike to Maxwellian-like with the increase in low-frequency power. In the earlier experimental results, the Maxwellian [25] or bi-Maxwellian [26] electron energy distribution functions were measured in γ mode. Secondary electron emission from the electrode by ion bombardment may result in intensive ionization and charge multiplication as the emitted electrons are accelerated in the large electric fields within the rf sheath, accompanied by a growth in plasma density (figure 3(a)) and a drop in electron temperature (figure 3(b)).…”
Section: Resultsmentioning
confidence: 99%